Management of first trimester miscarriage after implementation of a standardized protocol in a tertiary hospital in Cape Town, South Africa – an observational study - Breidenthal, Anne Guri (Stellenbosch : Stellenbosch University, 2017)
Thesis (MMed)--Stellenbosch University, 2017.